2020
DOI: 10.3390/rs13010020
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Unmanned Ground Vehicle and LiDAR Pipeline for the High-Throughput Phenotyping of Biomass in Perennial Ryegrass

Abstract: Perennial ryegrass biomass yield is an important driver of profitability for Australian dairy farmers, making it a primary goal for plant breeders. However, measuring and selecting cultivars for higher biomass yield is a major bottleneck in breeding, requiring conventional methods that may be imprecise, laborious, and/or destructive. For forage breeding programs to adopt phenomic technologies for biomass estimation, there exists the need to develop, integrate, and validate sensor-based data collection that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…The difference in rolling resistance or traction in the wheels of a differential drive robot can make the robot turn unexpectedly, making the robot less precise in steering control. Some wheeled robots use two wheels for steering and two wheels for driving (2WD2WS) [31,34]. The locomotion is controlled by the forward/backward speed and turning angle, similar to an Ackermann steering, enabling precise steering control.…”
Section: Mobile Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in rolling resistance or traction in the wheels of a differential drive robot can make the robot turn unexpectedly, making the robot less precise in steering control. Some wheeled robots use two wheels for steering and two wheels for driving (2WD2WS) [31,34]. The locomotion is controlled by the forward/backward speed and turning angle, similar to an Ackermann steering, enabling precise steering control.…”
Section: Mobile Platformmentioning
confidence: 99%
“…Plant height and row spacing estimation [58] DairyBioBot [34] RTK-GNSS Ryegrass Ryegrass biomass estimation [34] 7 Plant Phenomics Development of row-following algorithm in polytunnels [60] Ladybird [37] RGB camera2D LiDAR Hyperspectral camera…”
Section: Cornmentioning
confidence: 99%
“…Over the years UGVs (Unmanned Ground Vehicles), also known as UTVs (Unmanned Terrestrial Vehicles) or USVs (Unmanned Surface Vehicles) have been developed and used in many fields for several different applications, ranging from the automation of farm tasks and the precision agriculture field (Bechtis et al, 2017) to mine inspection (Szrek et al, 2020). Moreover, mobile terrestrial systems are recently reported to be increasingly used for agricultural science applications (Nguyen et al, 2020). Moreover, mobile robots have been exploited for search and rescue (SAR) operations in various dangerous environments, to enhance efficiency but also to improve the safety of the rescue personnel.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been addressed in the field of robotics for many years under the concept of Simultaneous Localization and Mapping (SLAM) [15]. Consulted applications use the generated point clouds for fruit detection, yield prediction [14], canopy characterization [16], automatic panicles detection [17], high-throughput phenotyping [5,18], low cost phenotyping [16], and fast phenotyping [19], among others. Table 1 summarizes the applications, crops, and used sensors on recent works.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the applications, crops, and used sensors on recent works. High-throughput phenotyping Maize 3D Velodyne HDL64-S3 GNSS receiver with two antennas UGV [5] Ryegrass 2D SICK LMS-400 Here+ V2 RTK GPS UGV [18] The development of a high-resolution phenotyping platform integrated with postprocessing technology offers the opportunity to assess complex traits more effectively. Compared to other platform types, UGVs reduce personnel time to cover large test plots and provide more accurate measurement because they can operate at constant speed and avoid human error.…”
Section: Introductionmentioning
confidence: 99%